Tools for regulating metabolic diseases: extracellular vesicles from adipose macrophages - Liang Zhang; Kecheng Lou; Yunmeng Zhang; Yuanjing Leng; Yuqing Huang; Xinxin Liao; Xiaoliang Liu; Shangzhi Feng; Guoqiang Feng (Frontiers in Endocrinology)
Metabolic diseases have gradually become one of the most significant global medical burdens. Diseases such as obesity, diabetes, and metabolic syndrome, along with their complications, are clinically categorized as metabolic diseases. Long-term oral medication significantly reduces patient compliance and quality of life. Therefore, alternative therapies that intervene at the cellular level or target the root causes of metabolic diseases might help change this predicament. Research has found that extracellular vesicles derived from adipose macrophages can effectively regulate metabolic diseases by influencing the disease’s development. This regulation is likely related to the role of these extracellular vesicles as important mediators in modulating adipose tissue function and insulin sensitivity, and their involvement in the crosstalk between adipocytes and macrophages. This review aims to describe the regulation of metabolic diseases mediated by adipose macrophage-derived extracellular vesicles, with a focus on their involvement in adipocyte crosstalk, the regulation of metabolism-related autoimmunity, and their potential as therapeutic agents for metabolic diseases, providing new avenues for diagnosis and treatment.